Prevalences of diabetic foot ulcer and foot self-care practice, and associated factors in adult patients with diabetes in south-east Ethiopia. Issue 10 (October 2022) - Negash, Wogene; Assefa, Tesfaye; Sahiledengle, Biniyam; Tahir, Anwar; Regassa, Zegeye; Feleke, Zegeye; Regasa, Tadele; Tekalegn, Yohannes; Mamo, Ayele; Teferu, Zinash; Solomon, Damtew; Gezahegn, Habtamu; et al.
Objective: We aimed to assess the prevalences of foot ulcer and foot self-care practices, and identify associated factors in adult patients with diabetes attending a referral hospital in south-east Ethiopia. Methods: We performed a cross-sectional study of 267 diabetic patients. Multivariable binary logistic regression was used to identify factors associated with diabetic foot ulcer and foot self-care practice. Results: The prevalence of diabetic foot ulcer was 11.2% (95% confidence interval [CI] 7.42–15.05). One hundred and forty-four (53.9%; 47.9, 59.9) patients demonstrated good foot self-care. Living rurally (adjusted odds ratio 2.27; 95% CI: 1.86–6.97), lack of regular exercise (3.91; 1.51–10.10), peripheral neuropathy (2.77; 1.05–7.33) and foot calluses (5.69; 1.74–18.59) were associated with diabetic foot ulcer. Urban inhabitants (2.01; 1.09–3.69), patients with diabetes for >10 years (2.92; 1.48–5.77), women (2.95; 1.66–5.22), and patients with a glucometer at home (2.05; 1.09–3.85) were more likely to have good foot self-care practice. Conclusion: The prevalence of diabetic foot ulcer was 11.2%. This prevalence is lower than those identified in other Ethiopian studies. However, patient awareness regarding foot self-care practice and risk reduction should be improved.